PENGARUH HARGA PSIKOLOGIS TERHADAP ETIKA BISNIS - SRI RAMADHAN (Maqdis: Jurnal Kajian Ekonomi Islam, 2016)
Article examines the issue of psychological pricing. The formulation of the research is whether the psychological price already meet the criteria for a fair price and not contrary to business ethics in Islam. Research is a research library. The study is qualitative. The research approach is hermeneutic data analysis technique used is descriptive-analysis-critical. The study's findings are a) The relationship between ethics and business is something that cannot be separated from each other, and b) pricing of psychological conflict with Islamic business ethics.